PENGARUH EKSPOR NETTO DAN CADANGAN DEVISA TERHADAP JUMLAH UANG BEREDAR DI INDONESIA TAHUN 1991-2009 - Doris Melika Samosir (Department of Development Economics, Universitas Sriwijaya, 2012)
This study aims at identifying and analyzing the influence of net exports and foreign exchange reserves on the money in motion (M2) in the period of 1991-2009 in Indonesia. The secondary data were collected from Indonesia Central Office of Statistic, Indonesia Monetary Statistic and Financial Reports of Bank of Indonesia. This research used the Ordinary Least Square (OLS) method for the analysis of the data. In the model, M2 was the dependent variable whereas the net exports and the foreign exchange reserves were the independent variable. The analysis states that M2 was influenced by the net exports and the reserves. The result show that the net exports and the foreign exchange reserves influenced on M2 significantly as indicated by R2 value of 0,06409. This means that 64,09 % increase of M2 was determined by the net exports and the foreign exchange reserves, and the rest of 35,91 % was determined by other factors. In the words, the exports and the reserves influenced on M2 simultaneously and significantly as shown by (M2) F –obtained > F –table (12.49855 > 3.59). Keywords: Money In Motion (M2), Net Exports, Foreign Exchange Reserves